Oedipal fragments: Reconsidering the significance of Oedipus for James Bernauer and Michel Foucault. (October 2021) - McCall, Corey
This essay reconstructs James Bernauer's reading of Foucault's critique of psychoanalysis in his essay "Oedipus, Freud, Foucault" in order to assess the role that Foucault's critique of psychoanalysis and his reading of Oedipus play in Bernauer's account of Foucault's ethics. Along the way, it traces a shift in Foucault's reading of Oedipus in terms of power and knowledge in Lectures on the Will to Know to rituals of truth or alethurgy in On the Government of the Living. Finally, based on this reading it argues that this shift is relevant for understanding Foucault's turn toward ethics and practices of the self in his final writings.